Lumbar Microdiscectomy. Retrospective Analysis of the Results of Treatment of 54 Patients - Uleshchenko, D.V.; Stashkevych, A.T.; Bublyk, L.O.; Shevchuk, A.V. (TERRA ORTHOPAEDICA, 2021)
Summary. Although the microdiscectomy techniques for surgical treatment of a herniated disk are improved, the share of poor outcomes after the lumbar pain syndrome treatment remains high. Objective: to improve the outcomes of patients with lumbar spine osteochondrosis complicated with a herniated disk. Materials and Methods. The retrospective analysis of 54 patients with a lumbar herniated disk, who underwent surgical treatment from 2019 till 2020 at the Spine Surgery Department of the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine”. The age of patients varied from 23 to 78 years (mean age – 41.1±11.7 years). Results. We assessed the outcomes using VAS, Oswestry, and Nurick scales on the first day after the surgery, one month, and six months after it. VAS of the lower back pain syndrome declined on average from 5.9±1.59 to 3.4±1.55 on the first day after the surgery, to 1.7±1.1 in a month, and to 2.5±2.1 six months after the surgical treatment. The surgery eliminates radiculopathy and reduces radicular pain according to VAS on average from 8.5±1.17 to 1.3±1.04 on the first day after the surgery, to 1.5±1.0 in a month, and to 1.4±1.6 six months after it. The quality of life according to ODI improved on average from 74.4±5.12 before the surgery to 29.7±9.6 in a month and to 9.6±9.2 six months postoperatively. As of the discharge, 55.6% of patients demonstrated their nervous system’s function recovered to the stage I and 38.9% – to the stage II. The long-term follow-up has shown positive dynamics in all the patients: the complete regress of neurologic symptoms in 74.4% and improved conditions – in 25.6% of patients. Conclusions. Surgical treatment of a herniated lumbar disk with the microdiscectomy method ensures the fulfillment of the fundamental nerve rootlet decompression by fenestrotomy, disctomy, or discectomy, and excision of the hernia, including sequestrated one. The positive dynamics of the pain syndrome scores, life quality, and neurological disorders is significant (р<0.05) and substantiates the efficiency of the treatment.